The measurement of dielectric properties of leucaena leucocephala biocomposite antenna substrate in water immersion condition / A. A. Azlan, M. T. Ali and M. F. Jamlos - Azlan, A. A.; Ali, M. T.; Jamlos, F. (UiTM Press, 2016)
This paper contributes the dielectric properties measurements on five mixture of biocomposite antenna substrates in water immersion condition. The fabrications process of the biocomposite antenna substrate uses the compounding flat press method between the Polypropylene acting as laminator and stem three of Leucaena Leucocephala as a filler. The dielectric properties measurements conducted by using the KEYSIGHT 85070E coaxial probe method, with the observe frequency range of 1 GHz to 20 GHz and ASTM D570 procedure for water immersion process. The percentages of the water absorption rate reported 0.026 % (PP100), 0.18 % (PB9010), 0.22 % (PB8020), 0.28% (PB7030) and 0.35 (PB6040), while the changes of the dielectric properties reported increase 10.31 % (PP100), 11.16 % (PB9010), 15.48 % (PB8020), 23.60 % (PB7030) and 36.35 % (PB6040) when compared with the dielectric properties measurements before 24 Hours ASTM D570 water immersion procedure. The changes of the water absorption rate and dielectric properties percentages in line with the increments of filler composition mixture. The data from this measurement useful to observe the aging shielding capability of the material against water and moisture content absorption for antenna substrate material.